Nursing students' perception regarding borderline personality disorder (Research, Society and Development, 2023)
The objective of the work was to assess the knowledge of nursing students regarding borderline Personality Disorder. This study was conducted through an online survey provided by the "Google Forms" platform to students from a private University Center in Curitiba. Twenty-seven nursing students from the 7th semester and above participated during the month of October 2023. As a result, it was observed that the majority of interviewed students reported being familiar with borderline Personality Disorder and claimed to have had or currently have subjects related to mental health. Regarding the causes, consequences, and manifestations of the disorder, most were unable to respond specifically and could not probe or detail their answers more precisely. We can conclude that borderline Personality Disorder is present, but students' knowledge about it is not yet adequately satisfactory. Therefore, there is a need to deepen the topic in classrooms, academic internships, expanding scientific knowledge, and promoting the improvement and training of professionals in the field. This way, students can become capable of welcoming and dealing with the social, pathological, environmental, and contextual conditions in which their patients are immersed.